Discovery of highly potent and selective phosphatidylinositol 3-kinase-δ inhibitors for the treatment of blood cancers and autoimmune diseases - Buzrieda, Anas (2021)
Phosphatidylinositol-3-kinase (PI3K) are a group of the lipid kinases superfamily, that play a crucial role in signalling pathways involved in the regulation of numerous cellular processes such as survival, growth, proliferation and differentiation. PI3K δ belongs to the class-IA subset of PI3Ks and is mainly present in leukocytes, where it regulates the development and function of adaptive immune cells (the B and T lymphocytes). However, PI3K δ dysregulation is implicated in human diseases, including blood cancers such as leukaemia and autoimmune diseases such as rheumatoid arthritis. The selective inhibition of PI3K δ may therefore provide an exciting therapeutic opportunity to treat different types of haematological malignancies and autoimmune disorders.